If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x-23=-16-3x-(-9)
We move all terms to the left:
-5x-23-(-16-3x-(-9))=0
We calculate terms in parentheses: -(-16-3x-(-9)), so:We get rid of parentheses
-16-3x-(-9)
determiningTheFunctionDomain -3x-16-(-9)
We add all the numbers together, and all the variables
-3x-7
Back to the equation:
-(-3x-7)
-5x+3x+7-23=0
We add all the numbers together, and all the variables
-2x-16=0
We move all terms containing x to the left, all other terms to the right
-2x=16
x=16/-2
x=-8
| x6-5=x5 | | 9-6u=63 | | 17(7-2n)=-11(6n+1)+8 | | -2+5k=48 | | 7+4+x=18 | | 54+25c=1 | | 54=25c=1 | | 1=28c+54 | | 2^(2x)-3*4^(x-1)=2 | | (x-4)=3/4x+4 | | 11a+35a=415 | | 7x+12(45-7x)=52 | | 8(x-2)=(7x+1 | | s+42=59 | | t-13=45 | | 7=k/3 | | f+2=64 | | 17=u-44 | | v-9=50 | | -7w+6=-50 | | w+75=86 | | n+78=88 | | 7x=12=9x-13 | | 62=v+6 | | 1+33c=12 | | 5x2-55x=140 | | 60+(x+40)+x=180 | | 10=1.5x+5+0.5x+x | | -14k+5k=-9k | | 6x+9x+x-30+25=x+2x+80 | | X^2-4x=49 | | 0.20x=-23 |